Shear-wave velocity structure underneath the city of Padang, Indonesia - Liang, Huikai. (2011)
Field observations were done and microtremor recordings were taken from various sites in Padang and Pariaman from 16th August 2010 to 26th August 2010, and they would be processed using the Spatial Autocorrelation (SPAC) method.MSM have become increasingly popular among researchers as compared to conventional methods such as borehole drilling, as a result of its relatively low cost, time saving and non-destructive advantage. With limited borehole data of Padang available, this report would provide potential researchers a more comprehensive knowledge on the subsurface profile of Padang. The method made use of microtremor sensors set up in array configurations to record microtremor wave amplitudes which was then used to process Rayleign waves dispersion curves and generate the subsurface soil layers for the various sites set up in various parts of Padang.